Novel insights into how autophagy regulates tumor cell motility. Issue 9 (1st September 2016) - Mowers, Erin E.; Sharifi, Marina N.; Macleod, Kay F.
ABSTRACT: Metastasis requires tumor cells to overcome a series of challenges to successfully travel to and colonize new microenvironments. As an adaptive (or maladaptive) response to stress, macroautophagy/autophagy has garnered increasing interest with respect to cancer metastasis, supported by clinical observations of increased autophagic flux in distant metastases relative to primary tumors. Recently, we identified a new role for autophagy in tumor cell motility through the turnover of focal adhesions, large multi-protein structures that link extracellular matrix-bound integrins to the cytoskeleton. The disassembly of focal adhesions at the cell rear is critical to forward movement and successful migration/invasion. We demonstrated that the focal adhesion protein PXN (paxillin), which serves as a crucial scaffolding and signal integrator, binds directly to LC3B through a conserved LC3-interacting region (LIR) motif to stimulate focal adhesion disassembly and metastasis and that this interaction is further promoted by oncogenic SRC.